2020
DOI: 10.3390/ijerph17176191
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Injury and Overload among Amateur Marathoners as Indicated by Changes in Concentrations of Cardiovascular Biomarkers

Abstract: Marathons continue to grow in popularity among amateurs. However, the impact of intensive exercise on the amateur’s cardiovascular system has not yet been studied. Analysis of the influence of the marathon on kinetics of biomarkers reflecting cardiac injury and overload may bring new insights into this issue. We investigated the effect of running a marathon on the concentrations of high sensitivity cardiac troponin I (hs-cTnI), heart-type fatty acid binding protein (H-FABP), N-terminal proatrial natriuretic pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…After the finishing the marathon run, we asked the participants to suspend high-intensity training as well as participation in any upcoming competitions. The characteristics of a study group were described previously [7].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the finishing the marathon run, we asked the participants to suspend high-intensity training as well as participation in any upcoming competitions. The characteristics of a study group were described previously [7].…”
Section: Methodsmentioning
confidence: 99%
“…Fasting blood samples at Stage 1 and Stage 3 were collected at the cardiology department. Serum was prepared immediately after collection by centrifugation at 2000 rpm at room temperature for 12 minutes and then stored in -80˚C for the further analysis [7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myocardial injury has also been documented as a transient phenomenon after high-intensity exercise [ 52 , 53 ]. Troponin concentrations are higher after short intense periods of exercise than following prolonged exercise at lower intensity, and in healthy persons levels return to pre-exercise levels within 24 h. Elevation in both troponin I and T has been documented in athletes and non-athletes after major endurance events, with up to 43% of non-athletes having concentrations above the 99th percentile [ 54 , 55 , 56 ]. Historically, rhabdomyolysis, which can occur after intense exercise or muscle injury, has been positively correlated with elevated cardiac troponins [ 57 ].…”
Section: Mechanisms Of Myocardial Injurymentioning
confidence: 99%
“…Although the rise in GDF15 may be related to changes in cardiac hemodynamic volume and pressure overload immediately after the marathon, it has been proposed that GDF15 does not appear as reliable to track specifically cardiorespiratory fitness in acute exercise, possibly because of the contribution of other noncardiac processes to the GDF15 rise in exercise (Kaleta-Duss et al, 2020). Nonetheless, some authors found GDF15 levels to be associated with impairment in exercise capacity in patients with the heart failure syndrome (Stahrenberg et al, 2010) whereas others do not consider GDF15 as a reliable biomarker of exercise capacity in heart failure patients (Fudim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%